1991
DOI: 10.1007/bf01658980
|View full text |Cite
|
Sign up to set email alerts
|

Lower esophageal sphincter characteristics and esophageal acid exposure following partial or 360‡ fundoplication: Results of a prospective, randomized, clinical study

Abstract: In a prospective, randomized, clinical trial, we compared a partial (180-200 degrees, Toupet) with a total fundoplication (360 degrees, Rossetti) in the surgical treatment of gastroesophageal reflux disease. Seventy-one patients entered the trial; 33 were allocated to a partial fundoplication and 38 to a 360 degrees fundic wrap. Each patient was investigated prior to as well as 3 and/or 6 months after the operation, including an endoscopic and clinical assessment. Manometry was carried out via a triple lumen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
2
4

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 27 publications
6
36
2
4
Order By: Relevance
“…Six dealt with open fundoplication: 1 from Honolulu, USA; 44 1 multicenter from France; 45 1 from Stockolm, 46 and another from Goteborg, [47][48][49][50][51][52] Sweden; 1 from Liverpool, UK; 53 and 1 from Santiago, Chile. 54 The remaining 3 trials dealt with laparoscopic fundoplication: from Birmingham, USA; 55 from Adelaide, Australia; 56 and from Hamburg, Germany.…”
Section: Partial Versus Total Wrapmentioning
confidence: 99%
“…Six dealt with open fundoplication: 1 from Honolulu, USA; 44 1 multicenter from France; 45 1 from Stockolm, 46 and another from Goteborg, [47][48][49][50][51][52] Sweden; 1 from Liverpool, UK; 53 and 1 from Santiago, Chile. 54 The remaining 3 trials dealt with laparoscopic fundoplication: from Birmingham, USA; 55 from Adelaide, Australia; 56 and from Hamburg, Germany.…”
Section: Partial Versus Total Wrapmentioning
confidence: 99%
“…Many report that after various antireflux procedures a great majority of patients can vent air from the stomach. Consequently when we specifically asked our patients whether they were able to belch after surgery, we found similar results and no difference between total and posterior partial fundoplication [99,100]. However, when we carefully examined these patients, we found that the latter less frequently complained of socially embarrassing flatulence due to a greater ability to vent air from the stomach.…”
Section: Complications Of Antireflux Surgerymentioning
confidence: 50%
“…Open 18 16 180º posterior 2 years Lundell et al (21,22) Hagedorn et al (15) Open 54 56 180º posterior 11 years…”
Section: Methodsunclassified